2000
DOI: 10.1177/0743558400151003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Complexity of Expectations and Adjustment to University in the First Year

Abstract: Expectations about university and subsequent adjustment in the first year were examined in a longitudinal study of the transition to university. Two hundred and twenty-six students (158 females and 68 males) completed a preuniversity questionnaire in the summer prior to beginning university, and another questionnaire in February of their first year. The preuniversity questionnaire contained measures that assessed perceived stress and the amount and sources of information students had about university, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 29 publications
(37 reference statements)
7
102
1
11
Order By: Relevance
“…Responsibilities of independent young adults must be taken on, although they are still in the late adolescence phase of their development. Subsequently, they experience IADL challenges such as managing their own finances, grocery shopping, meal preparation, and doing their own laundry 2,14 , all of which are time consuming. These expectations present much larger challenges than what they had anticipated and exacerbate the already heavy academic workload that has to be managed 14 .…”
Section: Instrumental Activities Of Daily Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsibilities of independent young adults must be taken on, although they are still in the late adolescence phase of their development. Subsequently, they experience IADL challenges such as managing their own finances, grocery shopping, meal preparation, and doing their own laundry 2,14 , all of which are time consuming. These expectations present much larger challenges than what they had anticipated and exacerbate the already heavy academic workload that has to be managed 14 .…”
Section: Instrumental Activities Of Daily Livingmentioning
confidence: 99%
“…This can cause stress for the first-year student, thus influencing their academic performance 34,14,18 . Pancer et al…”
Section: Financial Stress -Managing My Finances… Food and Living Expementioning
confidence: 99%
“…Pancer et al (2000) found that if a student had a complex expectation of what university would be like before they started, they were more likely to cope when there. Tomas' story is contrary to this, suggesting that a student with a complex expectation of university in reality found university life unchallenging, making it difficult for them to cope with the lack of challenge.…”
Section: Ii) Being Academic -Connection Through Disconnectionmentioning
confidence: 99%
“…Já ao nível das expectativas, os estudos evidenciam a sua influência no sucesso e na adaptação académica (Fernandes & Almeida, 2005;Pancer, Hunsberger, Pratt & Alisat, 2000). Esta expetativa constitui uma variável importante na adaptação ao novo contexto universitário, pressupondo, para esta adaptação, que o estudante adeque atitudes e comportamentos académicos (Saavedra, Loureiro, Silva, Faria, Ferreira, Taveira, Araújo, Faria, Araújo, & Vieira, 2011).…”
Section: Introductionunclassified